The Effects of Alcohol on a Subject with Suspected Spasmodic Dysphonia - Whitney, Chitty (My University, 2010)
Numerous factors influence spasmodic dysphonia, with emotional stress, anxiety, and physical effort making it worse. Alcohol is usually a depressant to the nervous system, calming and relaxing the partaker. Since stress and anxiety have been shown to affect spasmodic dysphonia and alcohol is known for the relaxation of muscles, this study questions the effect of alcohol on the fundamental frequency, pitch range and phonic breaks of a subject with suspected spasmodic dysphonia. Implications and recommendations are presented.
Keywords: Alcohol; Communication Sciences